COVID-19 and Food Safety FAQ: Shopping and Handling Groceries - Michelle Danyluk; Natalie Seymour; Mary Yavelak; Candice Christian; Ben Chapman (EDIS, 2020)
This new one-page flyer answers food safety questions about preventing COVID-19 transmission when grocery shopping and handling groceries. Written by Natalie Seymour, Mary Yavelak, Candice Christian, and Ben Chapman (NC State University Extension) and published by the UF/IFAS Food Science and Human Nutrition Department.